2020
DOI: 10.1007/s12015-020-09995-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Importance of Survivin in Stem Cells and Cancer: the Development of New Cancer Therapeutics

Abstract: Survivin is one of the rare proteins that is differentially expressed in normal and cancer cells and is directly or indirectly involved in numerous pathways required for tumor maintenance. It is expressed in almost all cancers and its expression has been detected at early stages of cancer. These traits make survivin an exceptionally attractive target for cancer therapeutics. Even with these promising features to be an oncotherapeutic target, there has been limited success in the clinical trials targeting survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 260 publications
(294 reference statements)
0
51
0
5
Order By: Relevance
“…Consistently, in cancer cells, the Telomerase allows uncontrolled cell proliferation, which is essential for tumor progression (80). Additionally, Survivin, a protein overexpressed in many cancers (81), where it promotes proliferation and inhibits apoptosis, is expressed in trophoblast cells, however its role in this location has not been elucidated yet (82,83). Altogether these studies indicate that the Telomerase and Survivin have an important role in cell proliferation in both trophoblast and cancer cells.…”
Section: Similarities and Differences Between Cancer Cells And Trophoblast Derived Cells Cellular Proliferation Migration And Invasionmentioning
confidence: 93%
“…Consistently, in cancer cells, the Telomerase allows uncontrolled cell proliferation, which is essential for tumor progression (80). Additionally, Survivin, a protein overexpressed in many cancers (81), where it promotes proliferation and inhibits apoptosis, is expressed in trophoblast cells, however its role in this location has not been elucidated yet (82,83). Altogether these studies indicate that the Telomerase and Survivin have an important role in cell proliferation in both trophoblast and cancer cells.…”
Section: Similarities and Differences Between Cancer Cells And Trophoblast Derived Cells Cellular Proliferation Migration And Invasionmentioning
confidence: 93%
“…Survivin (encoded by the BIRC5 gene) is an anti-apoptotic protein often over-expressed in various cancer types and absent or little-expressed in normal cells [55]. Survivin depletion generally promotes tumor cell apoptotic death, and survivin is therefore recognized as an important therapeutic target [55][56][57]. We reported that…”
Section: Bpep and Dpep Deplete Anti-apoptotic Protein Survivin And Reduce Expression Of Direct Atf5 Targets Bcl2 And Mcl1mentioning
confidence: 99%
“…Literature reviews have shown that PI3-K [ 13 16 ], survivin [ 17 , 18 ] and MAP-K activation [ 19 , 20 ] are essential for cell proliferation. It is also possible that inhibition of MMP20 may inactivate the WNT / ß-catenin signalling pathway [ 19 ] leading to reduction in cell proliferation.…”
Section: 0 Discussionmentioning
confidence: 99%